Effect of the use of natural gas-diesel fuel mixture on performance, emissions, and combustion characteristics of a compression ignition engine - Karagoz, Yasin; Sandalci, Tarkan; Koylu, Umit O.; Dalkilic, Ahmet Selim; Wongwises, Somchai (SAGE PUBLICATIONS LTD, 2016)
A compression ignition engine with a mechanical fuel system was converted into common rail fuel system by means of a self-developed electronic control unit. The engine was modified to be operated with mixtures of diesel and natural gas fuels in dual-fuel mode. Then, diesel fuel was injected into the cylinder while natural gas was injected into intake manifold with both injectors controlled with the electronic control unit. Energy content of the sprayed gas fuel was varied in the amounts of 0% (only diesel fuel), 15%, 40%, and 75% of total fuel's energy content. All tests were carried out at constant engine speed of 1500r/min at full load. In addition to the experiments, the engine was modeled with a one-dimensional commercial software. The experimental and numerical results were compared and found to be in reasonable agreement with each other. Both NOx and soot emissions were dropped with 15% and 40%, respectively, energy content rates in gas-fuel mixture compared to only diesel fuel. However, an increase was observed in carbon monoxide emissions with 15% natural gas fuel addition compared to only diesel fuel. Although smoke emission was reduced with natural gas fuel addition, there was a dramatic increase in NOx emissions with 75% natural gas fuel addition.
Keywords: Diesel engine; natural gas; emissions; NOx; smoke; engine performance; EXHAUST EMISSIONS; HYDROGEN; MODE; Thermodynamics; Engineering